PESAN MORAL DIBALIK KISAH NABI MUSA DAN NABI KHIDIR DALAM QS. AL-KAHFI: (Studi Atas Penafsiran al-Razi dalam Mafatih al-Ghayb) - A. Halil Thahir; Ahmad Mughni Khoiruddin (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
The story of Prophet Musa and Prophet Khidir is one of the stories that is quite representative of the stories contained in the Al-Qur'an. The narrative description in the Al- Qur'an is certainly interesting to study. In presenting the story, al-Qur'an often uses metaphorical language and analogy which is alleged to be able to bridge the limited human ratio with the language of the al-Qur'an which is completely unlimited. This article examined the moral message behind the story of Prophet Musa & Prophet Khidir according to Fakhruddin al-Razi in his Tafsir, Mafa> tih al-Ghayb. This research was included in the literature review which was presented using the maudu'i interpretation method and Gadamer's philosophical hermeneutic approach. Based on the search, it was found that in interpreting this story, al-Razi considered a number of aspects such as internal relationships (aspects of munasabah) and the external context of the text (asbabun nuzul). In addition, based on Gadamer's theory of historical consciousness (awareness of historical influences), al-Razi was still influenced by his background as an ash'ariyyah. The reinterpretation of three important events in this story sequence shows the moral message of the story about the importance of tawadu’(humility), so that humans are always able to guard their behaviuor from being arrogant (takabbur), be patient in facing all tests and are determined.